The trait anger affects conflict inhibition: a Go/Nogo ERP study - Yong eLiu; Xianghong eZhan; Wei eLi; Heyun eHan; Huixia eWang; Junlin eHou; Guoli eYan; youjie ewang (Frontiers in Human Neuroscience, 2015)
To explore the time course of inhibitory control in high trait anger individuals, we recorded and analyzed ERP data relevant to visual Go/Nogo task in high and low trait anger participants. Compared with low trait anger participants, high trait anger participants revealed faster RTs in the Go/Nogo task. The nogo effect of N2 related to conflict monitoring was similar between two groups. While the P3go was larger in high than low trait anger groups, the P3nogo did not differ between two groups. This induced the smaller nogo effect of P3 in high than that in low trait anger group, which is closely related to the actual inhibition of the motor system. These data suggest the reduced later stage of inhibitory processes in high trait anger individuals, implicating the dysfunction of inhibitory control.